Interactive whiteboard (IWB) effectiveness in vocabulary achievement and motivation: Saudi EFL Learners’ Perceptions and Insights - Ahmad, Waqar; Zuraina, Ali (Rafaad, 2019)
English language teaching in Saudi Arabia has witnessed an enormous change with the introduction of modern technological equipment in the preparatory year program in Saudi universities. The new generation of digital natives have certain expectations about the use of technology, such as the Interactive Whiteboard (IWB) in their EFL classrooms. The current research study conducted at a Saudi university, involving two intact groups from the preparatory year EFL learners, aimed at understanding the perceptions and insights of the learners while providing them intervention with the help of Interactive Whiteboard (IWB) for 6 weeks. The data was collected at the end of the intervention, through a Likert-scale questionnaire designed for this study. The data attained showed that Saudi EFL learners’ experiences about the effects of Interactive Whiteboard (IWB) on their vocabulary achievement and their motivation were positive. Whereas the experiences of both the male and female participants were similar.